Audience interaction with podcast content on digital platforms and its impact on the future of radio in the Arab region - Abdelhamid, Amr Mohamed Mahmoud (Dirasat: Human and Social Sciences, 2024)
Objective: This study aimed to monitor Arab region podcast listeners’ consumption behaviors and assess digital audio content creators’ adherence to professional standards. It explored their awareness of elements enriching podcasts and examined the impact on traditional radio amidst digital advancements. Methodology: The study adopted the Media Richness Theory and employed a survey method using a questionnaire applied to a purposive sample of 400 podcast listeners in the Arab region. Results: The study found a statistically significant correlation between the public’s perception of the media richness of podcasts and their assessment of content creators’ adherence to professional standards. Significant differences were also observed among respondents in terms of variables such as age, gender, and intensity of exposure to podcasts, particularly in their levels of perception of the richness of podcasts as a medium. However, no statistically significant differences were found between groups of respondents when considering variables such as gender, age, educational level, level of exposure to podcasts, and geographical area of residence in relation to their perception of the impact of podcast development on the role of radio as a traditional medium of audio broadcasting. Conclusion: Podcasts emerged as a rich form of digital media, distinct from traditional radio, yet the latter maintains trust and a diverse audience. Valuable insights for podcast producers were gleaned, guiding content creation aligned with audience preferences. The study emphasized the need for professional and ethical standards among Arab region podcast producers